Irrigação e certificação da cafeicultura na Região Centro-Oeste de São Paulo - Perdona, Marcos Jose [UNESP]; Soratto, Rogério Peres [UNESP]; Martins, Adriana Novais; Suguino, Eduardo; Cuzato Mancuso, Mauricio Antonio [UNESP] (Instituto Agronômico, 2012)
An unsatisfactory profitability has led to the gradual decline of the coffee plantations in São Paulo. Among the alternatives that arise for solving this problem, two stand out: the irrigation of crops and certification of properties. Even in areas considered suitable for cultivation of arabica coffee (Coffea arabica L.), the use of irrigation can promote an increase in grain yield. In addition, the product certification promotes their differentiation in the market and can improve the economic results of the activity. This study aimed to evaluate the development and productivity of coffee crops subjected to irrigation or not, comparing economic data in the marketing of coffee certified or not, under the conditions of the mid-west region of São Paulo state. The field experimental design was in randomized blocks with two treatments (with and without drip irrigation) and ten repetitions. The costs of production and profitability by selling the final product were calculated. The irrigation increased the development and productivity of coffee. The return on investment took place after the third harvest. Irrigation combined with the sale of certified coffee provided financial balance 1,192% higher than the coffee is not irrigated and non-certified.
Irrigation and certification on coffee crop in mid-west of São Paulo State, Brazil
Keywords: Coffea arabica L.; water deficit; drip; Fair trade; profitability